The startup community way evolving an entrepreneurial ecosystem - Feld, Brad; Hathaway, Ian (John Wiley & Sons, Inc., 2020)
"The Startup Community Way is a sequel to Startup Communities: Building an Entrepreneurial Ecosystem in Your City. It pciks up where Startup Communities left off, looking at why makes startup communties thrive -- anywhere. The Startup Community Way advances the practice of startup community building in several key ways: Establishes the very notion of a startup community. Provides an intro to relevant historical frameworks: agglomeration, networks, creative class Establishes the Boulder Thesis: a governing philosophy for startup communitie. Discusses the role of key stakeholders (leaders and feeders), what can go wrong (Classical Problems and Myths), why a community matters (Power of Community and Broadening), and why leaders are the key to bringing it all together (Attributes of Leadership). Offers a ton of practical advice along the way, aimed primarily at entrepreneur community builders. Expands the Boulder Thesis to benefit nascent startup communities or those in an international context. Discusses es the role of government (national, regional, local, international) in startup communities -- they can and do play a big role, particularly outside of the United States. Provides a framework or model for assessing and measuring the "maturity" of a particular startup community--"Where are we?" and "How do we get where we need to go?" Shares lessons that will be more generalizable across geographies and will tell lots of stories from around the United States and other countries. ?SCW will go deeper on other universities, other non-tech stuff, and structural dynamics (like technology transfer, patents, rules of engagement for students). It ill also develop a more robust framework for assessing and measuring a startup community (ranges from quality and types of stakeholders and assets to improving linkages and changing culture). ?Having the benefit of 6+ years to look back upon, SCW will have examples to draw upon from cities around the world -- a look back at what we have learned in the last half decade. In that regard, we'll have many more outside voices (contributors) in this book compared with SC1. ?The main new intellectual contribution of SCW is the introduction and application of "complex systems" theory into the practice of startup community building. SC1 is steeped in complexity theory, though does not go deep on explaining the implications of complex systems and how that justifies our recommendations (which differ widely from more traditional approaches). ?SCW will have a more robust/concise practitioners guide at the end"--